Hemophagocytic Lymphohistiocytosis Associated to Klebsiella pneumoniae Infection: A Case Report - Zhang, Zhiyu; Liu, Junqian; Wang, Jingyue; Wang, Yushi (Frontiers in Immunology, 2021)
A 73-year-old Chinese man, admitted to the cardiac intensive care unit (ICU) with fever and general pain, is reported on here. Based on the patient's initial condition of multi-organ function impairment and increased serum ferritin, and after a series of examinations, the patient was diagnosed with Klebsiella pneumonia-induced hemophagocytic lymphohistiocytosis (HLH). Meropenem and dexamethasone were used in combination to treat the patient, and the results were very successful. HLH induced by Klebsiella pneumoniae has not been reported on previously. In this case report, it is suggested that Klebsiella pneumoniae is a possible trigger of HLH, and a combination of antibiotics and corticosteroids can be effective in treating HLH. It is also recommended that doctors in the ICU of each department should pay attention to the role of hyperferritinemia in the diagnosis of HLH, and ICU admission teams should include ferritin in their monitoring.